Proceedings of the Ninth Annual International ACM Conference on International Computing Education Research 2013
DOI: 10.1145/2493394.2493403
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the learning progressions of computational thinking of primary grade students

Abstract: We introduce the Progression of Early Computational Thinking (PECT) Model, a framework for understanding and assessing computational thinking in the primary grades (Grades 1 to 6). The model synthesizes measurable evidence from student work with broader, more abstract coding design patterns, which are then mapped onto computational thinking concepts.We present the results of a pilot-test study of the PECT Model in order to demonstrate its potential efficacy in detecting both differences in computational thinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 12 publications
3
101
0
6
Order By: Relevance
“…Dr.Scratch is a web tool based on Hairball (Boe et al, 2013) that implements several CT assessment methods found in the research literature (Brennan & Resnick, 2012;Moreno & Robles, 2014;Seiter & Foreman, 2013;Wilson, Hainey, & Connolly, 2012;Wolz, Hallberg, & Taylor, 2011). The CT score that Dr.Scratch assigns to projects is based on the degree of development of following dimensions of the CT competence: abstraction and problem decomposition, logical thinking, synchronization, parallelism, algorithmic notions of flow control, data representation, and user interactivity.…”
Section: Methodsmentioning
confidence: 99%
“…Dr.Scratch is a web tool based on Hairball (Boe et al, 2013) that implements several CT assessment methods found in the research literature (Brennan & Resnick, 2012;Moreno & Robles, 2014;Seiter & Foreman, 2013;Wilson, Hainey, & Connolly, 2012;Wolz, Hallberg, & Taylor, 2011). The CT score that Dr.Scratch assigns to projects is based on the degree of development of following dimensions of the CT competence: abstraction and problem decomposition, logical thinking, synchronization, parallelism, algorithmic notions of flow control, data representation, and user interactivity.…”
Section: Methodsmentioning
confidence: 99%
“…This advice contrasts with the work of other researchers who have identified patterns in student-created programs as a means of evaluating their degree of programming sophistication [5,7] but have not used them as teaching aids. In the SGD classroom, CTPs provide a means for describing solutions without going to the level of detail that includes every programming primitive involved.…”
Section: Introductionmentioning
confidence: 58%
“…Most of all, while engaging in testing and evaluating practices, children need to reflect on what causes any mismatches between the intention of the programming and the actualized robot performance. This is the practice of debugging [66]. By detecting mismatches and correcting the programming errors that caused those mismatches, children can close the gap between the robots desired state and its observed state [48].…”
Section: Engineering Design Processmentioning
confidence: 99%